An incomplete education - Jones, Judy; Wilson, William 1948- (New York Ballantine Books, 1987)
What was so important about the Dred Scott decision? Why aren't all Shakespearean comedies necessarily thigh-slappers? What happened inside Plato's cave? What's the difference between a fade-out and a dissolve? Fission and fusion? Shi'ites and Sunnis? The apostles and the disciples? Is postmodernism dead or just having a bad hair day? And for extra credit, how do you tell deduction from induction? An Incomplete Education answers these and thousands of other questions with incomparable wit, style, clarity and brevity. American Studies, Art History, Economics, Film, Literature, Music, Philosophy, Political Science, Psychology, Religion, Science, and World History: Here's the bottom line on each of these major disciplines, distilled to its essence and served up with consummate flair. In this new edition you'll find up-to-the-minute analyses of the geopolitical situation in Eastern Europe, Indochina, and the Horn of Africa; the latest breakthroughs in cloning and gene splicing; brand-new takes on the economy, from disinflation to global competition; a look at the recent upheavals surrounding abortion rights, free speech, and the death penalty; and much, much more"--
D., 10/00
Keywords: Handbooks, vade-mecums, etc